TP025/#1399 Artistry-7: phase 3 multicenter study of nemvaleukin alfa plus pembrolizumab versus chemotherapy in patients with platinum-resistant epithelial ovarian, fallopian tube, or primary peritoneal cancer. (4th December 2022) - Herzog, Thomas; Hays, John; Moore, Kathleen; Konstantinopoulos, Panagiotis; Gilbert, Lucy; Monk, Bradley; O'Malley, David; Barlin, Joyce; Rege, Jessicca; Desai, Monali; Du, Yangchun; Dalal, Rita; et al.
Abstract : Objectives: ARTISTRY-7 is evaluating the novel engineered cytokine nemvaleukin alfa (nemvaleukin, ALKS 4230) in patients with gynecological cancers. Nemvaleukin was designed to selectively bind to the intermediate-affinity interleukin-2 receptor, preferentially activating antitumor CD8 + T and NK cells, with minimal regulatory T cell expansion. This selectivity may provide enhanced tumor killing and improved safety/tolerability versus high-dose interleukin-2. In ARTISTRY-1, 4 responses (2 complete, 2 partial) were observed with nemvaleukin+pembrolizumab in patients with platinum-resistant ovarian cancer. Methods: ARTISTRY-7 (NCT05092360 ) is a currently enrolling phase 3, multicenter, randomized study of nemvaleukin and/or pembrolizumab versus chemotherapy. Eligible patients have histologically confirmed epithelial ovarian (high-grade serous, endometrioid, clear cell), fallopian tube, or primary peritoneal cancer. Patients must have had ≥1 prior line of systemic therapy (platinum-sensitive setting), ≤5 prior lines (platinum-resistant setting), and prior bevacizumab, with radiographic progression on most recent therapy. Patients with primary platinum-refractory disease (progression on first-line platinum therapy) or primary platinum resistance (progression <3 months after first-line platinum therapy completion) are excluded. Approximately 376 patients are being randomized (3:1:1:3) to receive nemvaleukin 6 μg/kg intravenously (days 1–5) + pembrolizumab 200 mg intravenously (day 1) in 21-day cycles, pembrolizumab or nemvaleukin monotherapy, or chemotherapy. Primary endpoint is investigator-assessed progression-free survival (RECIST v1.1) in nemvaleukin+pembrolizumab versus chemotherapy arms. Secondary/exploratory endpoints include overall survival, other antitumor measures, safety, health-related quality of life, and pharmacokinetic/pharmacodynamic effects. Results: Trial in progress: there are no available results at the time of submission Conclusions: Trial in progress: there are no available conclusions at the time of submission